Pārtikas alerģijas prevelence un ar to saistītie riska faktori bērniem - Ahmad, Sohail (Latvijas Universitāte, 2010)
Food allergies affect approximately 6% of preschool-age children and 3% to 4% - of adults. Food-induced allergic reactions are responsible for different symptoms associated with skin, gastrointestinal and respiratory symptoms. Objectives My main objective was to compare the prevalence of food allergies in children in Pakistan and Latvian, and explore its relationship to various risk factors. Materials and methods  The prospective study was conducted by analyzing data on consecutive patients Okara district hospital in Pakistan. A second group of patients were from the Latvian. Children's parents completed a questionnaire on the presence of allergies in children and the various risk factors. Results Food allergy prevalence in children Latvian was 20.27% (15/74), while in Pakistan - 14% (7 / 50). Pakistan's total population of breast feeding duration was greater in patients without allergies as children with allergies (18 and 11mēneši). Latvian to children with allergies in the family often found in children with allergies as a negative family history (52% vs. 9%). Diarrhea during the first year of life more often observed in children with allergic Pakistani group, as patients from the Latvian 28.57% vs 0%. Conclusions and Recommendations  Food allergy prevalence of children in Latvia was higher than in Pakistan. Latvian children with a diagnosis of allergy was significantly more frequent family history of allergy, indicating not only genetic predisposition, but possibly a common family risk factors that should be explored further. In this study, breast feeding protective effect was seen only in children in Pakistan. Infectious diseases in the potential protective effect of allergies case to be investigated further.

Food Allergy, Defined as an adverse immune Response to food proteins, Affecto as Many as 6% of young children and 3% to 4% of adults. Food-induced allergic Reaction are Responsible for a Variety of symptoms involving the skin, gastrointestinal tract, and respiratory tract and Might BE caused by IgE-mediated and non-IgE-mediated (Cellular) Mechanism. Our Understanding of how food Allergy Represent an abrogation of normal oral tolerance is evolving. Although Any food CAN provoke a Reaction, relatively Few Foods are Responsible for the Vast Majority of significant food-induced allergic Reaction: milk, egg, Peanuts, tree nuts, fish, and shellfish. A systematics Approach to Diagnosis Includes a careful history, laboratory studies followed by, élimination diet, and often food Challenges to Confirm a Diagnosis. Currently, management of food allergies consists of educating the Patient to Avoid ingesting the allergen and Responsible to initiate therapy in case of an unintended ingestion. Objectives My main WAS the Objective Compare the prevalence of food Allergy in children in Pakistan and Latvia and to study the ITS association With the Environmental Risk Associated With a factor of the disease in children. Materials and Methods A prospective Study WAS done analyzing data of the Patient With Consecutive minor health Problems or coming for general check up to the District Hospital Okara, Pakistan. The Other set of data is from Latvia. A Questionnaire WAS given to Be filled by the Parent. Results In the Latvian sample (n = 74) Prevalence of Food Allergy WAS 20:27% (15/74), Which WAS non significantly lower compared to 14% (7 / 50) in Pakistan. Duration of Breast feeding significantly in WAS No longer in Patient Without Allergy compared to Without Patient Allergy (11months vs 18 months for). Children With Allergy in the family more often HAD Allergy Diagnosis compared to the children Without Allergy in the family (52% vs 9%). Diarrhoea During 1st Year of Life WAS observed more often in the sample Pakistan Than Latvian sample 28.57% vs 0%, (p = 0.03). Conclusions and Recommendations Prevalence of Food Allergy in children in Latvia WAS non-significantly Higher Than in Pakistan. Children With Allergy Diagnosis HAD significantly more often Allergy in family anamnesis in Latvia pointing Not only the Genetic predisposition But Also "some of their common Familiale Risk factor That Hubble BE Further studied. In a study THIS No longer duration of total Breast feeding in non allergic children WAS observed only in the Pakistan sample. A Possible protective effect of childhood Infections Towards Allergy Hubble BE Further studied.
Prevalence of Food Allergy and associated risk factors in children
Keywords: Medicīna